Commissioning of two different algorithms for stereotactic Radiosurgery M6 FI+ CyberKnife system - Mageshraja Kannan; Jefy Ninan; Prasobh Chandrasenan; Subodh Chandra Pande; Aditya Gupta; Harpreet Kaur; Ajay Khatri (International Journal of Medical Research and Review, 2018)
Introduction: Cyber Knife M6 FI+ a very precise robotic stereotactic radiosurgery system which is capable of delivering very high radiation dose to the tumour while minimizing radiation exposure to normal organs and tissues. MultiPlan treatment planning system is used with the CyberKnife unit and the algorithms used for optimization are Ray-Tracing and Monte Carlo. Our CyberKnife M6 FI+ system commissioning is done as per the vendor recommendation and meeting the local regulatory guidelines.Materials and Methods: Clinical beam data measurement is carried out using Radiation Field Analyzer, Diode E, Pinpoint chamber, Semiflex ionization chamber and Unidose E Electrometer. FC-65 ionization chamber used in absolute dose calibration. The mechanical accuracy of the robot and image stability was verified using Radiochromic film (EBT3), E2E and Iris QA toolkits along with software. StereoPHAN is used for the patient-specific QA point dose measurement.Results: Tissue phantom ratio, Off-centre ratio, Output factor, Percentage depth dose, open beam profile and absolute dose calibration are done as per the protocols. E2E performed for two different modes- static and motion. Iris aperture size measured for all the field sizes. The patient-specific QA delivered for both algorithms.Discussion: Clinical beam data measurements are within ±1% of composite data set, overall standard deviation for Output Factors of the fixed and Iris collimators are 0.0026 and 0.0063. The absolute dose was calibrated to 1cGy per MU. E2E, Iris QA and Laser and radiation coincidence values are within the tolerance. Patient-specific QA point dose measurement variation for Ray-Tracing and Monte Carlo is 3% and 2%.Conclusion: These exercises are mandatory to achieve the accurate, precise and high quality of treatment which also includes patient safety.